E‐Books, e‐publishers and e‐book builders for children - Shiratuddin, Norshuhada (Taylor & Francis Group, 2002)
Children too can now take advantage of e‐book technology.E‐book titles for children are becoming popular as more and more e‐publishers are producing and selling children's books.This paper discusses and presents some of the latest e‐books initiatives for children.Firstly, e‐book definitions are explained in two categories: concept and devices.Then their formats, active e‐publishers and examples are outlined.Next, book builders that allow users to build books while maintaining the book metaphor are discussed with particular attention to a book builder designed specifically for children.Fifteen children participated in an evaluation to verify the ease of use of the selected book builder.An ease of use index was constructed from the addition of four variables: learning time, questions asked during learning, book building time and questions asked during building.Finally, this paper concludes that children are very much at ease with e‐book technology.They are able to use e‐books and e‐book builder without much effort.